Penggunaan Media Pembelajaran Dan Kreativitas BelajarTerhadap Kemampuan Berfikir Kritis Pada Mata Kuliah Akuntansi Keuangan Syariah Mahasiswa Program Studi Pendidikan Akuntansi Universitas Muhammadiyah SurakartaTahun Akademik 2013 - Tia Yunanda Istiani, Anasta, Dr. Djalal Fuadi, M.M (2017)
Accounting Education Study Program, Faculty of Teacher This study aims to determine: 1) Influence of Learning Media Use to critical thinking ability, 2) Influence of learning creativity to critical thinking ability, 3) Influence of use of learning media and creativity learn to critical thinking ability. This type of research includes quantitative descriptive research with the conclusion through statistical methods. This study included population research with 84 respondents. The instruments used in this study are questionnaires and documentation. Questionnaire previously tested and tested the validity and reliability test. Data analysis techniques used are multiple linear regression analysis, t test, F test, determination coefficient (R2), predictor contribution (SR and SE). Regression analysis results obtained by regression equation; Y = 14,451 + 0,718X1 + 0,395X2. The equation shows that critical thinking ability is influenced by the use of learning media and student learning creativity. The conclusion that can be drawn is; 1) The use of learning media has a positive effect on critical thinking ability. It is based on regression analysis (t test) known that thitung> ttable is 8,753> 1,990 with significance value <0,05 and effective contribution (SE) equal to 45,8% and relative donation (SR) of 73%. 2) learning creativity has a positive effect on critical thinking ability. This is based on regression analysis (t test) tcount> ttable is 4.508> 2.037 with significance value 0,05 and effective contribution (SE) equal to 16,9% and relative contribution (SR) equal to 27%. The use of learning media and student learning creativity on critical thinking skills. This is based on the analysis of multiple linear regression variation (F test) known that Fcount> Ftable is 68,167> 3,109 with value of significance 0,05 and coefficient of determination (R2) equal to 62,7% indicate that the influence of learning media use and student's creativity toward Critical thinking ability is 62.7%. While the rest influenced by other variables. Keywords: use of learning media, learning creativity, critical thinking ability